Transformational Leadership of School Principals in Enhancing Teacher ‎Professionalism: A Qualitative Review in the Context of Islamic Education - Auni Luthfiah Nurfathina; Aanisah Agusnani Rizq; Achmad Zailani; Nirva Diana; Eti Hadiati (JPI: Jurnal Pustaka Indonesia, 2025)
Teacher professionalism plays a crucial role in improving educational quality, ‎particularly in Islamic education, which emphasizes the integration of pedagogical ‎competence, professional ethics, and spiritual values. One of the strategic factors ‎influencing teacher professionalism is school principal leadership, especially ‎transformational leadership that focuses on human resource development. This study ‎aims to comprehensively analyze the strategies of transformational leadership ‎practiced by school principals in enhancing teacher professionalism within the ‎context of Islamic education. A qualitative approach with a Systematic Literature ‎Review (SLR) design was employed by reviewing reputable scholarly articles ‎published between 2015 - 2025. Literature searches were conducted using Google ‎Scholar, Scopus, DOAJ, and Web of Science, applying systematic inclusion and ‎exclusion criteria. Data were analyzed using thematic content analysis to identify ‎dominant patterns and themes. The findings reveal that transformational leadership ‎in Islamic education is strongly integrated with prophetic values, namely amanah ‎‎(integrity), fathanah (intellectual wisdom), and tawaddhu (humility). These values are ‎reflected in three main leadership strategies: moral and ethical role modeling, ‎intellectual stimulation through value-based instructional innovation, and ‎individualized consideration focusing on teachers’ well-being and professional ‎development. The study highlights that transformational leadership in Islamic ‎education extends beyond performance improvement to encompass character ‎building and the reinforcement of Islamic identity. This research contributes ‎conceptually to the development of a contextual and value-oriented framework for ‎Islamic educational leadership‎.